2020
DOI: 10.1590/fst.10919
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sunflower oil bleaching parameters: using Response Surface Methodology (RSM)

Abstract: Bleaching is an important part of the oil refining process, in which pigments, impurities, traces of metals, and oxidative-molecular components of oils are removed. On this regard, the optimization of bleaching conditions can be effective to increase oil quality. On this study, de-gummed and neutralized sunflower oil was bleached at 80, 90, 100, 110, and 120 °C for 15, 25, 35, 45, and 55 min by acid-activated bleaching clay with the concentrations of 0.4, 0.6, 0.8, 1, and 1.2% under laboratory conditions. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The increasing bleaching earth concentration positively affected decreasing the PV at constant temperature and constant bleaching time. This result agrees with Sedaghat Boroujeni et al (2020) since they also reported that the increasing bleaching clay concentration resulted in lower PV levels. Our study detected higher PV levels when the bleaching duration was set longer at lower bleaching earth concentrations.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The increasing bleaching earth concentration positively affected decreasing the PV at constant temperature and constant bleaching time. This result agrees with Sedaghat Boroujeni et al (2020) since they also reported that the increasing bleaching clay concentration resulted in lower PV levels. Our study detected higher PV levels when the bleaching duration was set longer at lower bleaching earth concentrations.…”
Section: Resultssupporting
confidence: 92%
“…Since the PV is a measure of the oxidation level in terms of oxygen content especially found in hydroperoxides in oils, the PV analysis is critical to revealing the oil sample's oxidation status. The previous reports regarding the bleaching step during refining reveal the process efficiency in decreasing PV (Pestana et al, 2008;Sedaghat Boroujeni et al, 2020;Škevin et al, 2012;Strieder et al, 2017Strieder et al, , 2019. However, the thermal application that could reach 110-120°C will degrade such minor compounds as tocopherols, an essential bioactive compound in most vegetable oils.…”
Section: Introductionmentioning
confidence: 99%
“…There are vast numbers of studies on improving the bleaching process of oils. In all these studies, the type and amount of bleaching agent, mixing time, temperature and pressure are the parameters examined (Skevin et al, 2012;Salawudeen et al, 2014;Chew et al, 2017;Mustafa and Abusabah, 2019;Boroujeni et al, 2020. ) by keeping the conventional heating method as the same.…”
Section: Introductionmentioning
confidence: 99%
“…Crude oil contains undesirable impurities (e.g., free fatty acids, phospholipids, pigments) that negatively impact appearance, odor, flavor, safety, and stability. Oil refining is essential to eliminate these impurities by not removing desirable components (e.g., tocopherols and sterols) and increasing the shelf life and optimizing color, odor, and taste for maximal consumer acceptance (Karabulut et al., 2005; Lamas et al., 2016; Medina‐Juarez & Gamez‐Meza, 2011; Sadeghat Boroujeni et al., 2019; Vaisali et al., 2015).…”
Section: Introductionmentioning
confidence: 99%